<span>The <u>correct answers</u> are:
x=-3 and x=-8.
Explanation<span>:
We can first write this in standard form, ax</span></span>²<span><span>+bx+c=0. To do this, we will add 11x to both sides:
x</span></span>²<span><span>+24+11x=-11x+11x
x</span></span>²<span><span>+11x+24=0.
Now we can factor this. Look for factors of c, 24, that sum to b, 11. Factors of 24 are:
1 and 24 (sum 25)
2 and 12 (sum 14)
3 and 8 (sum 11)
4 and 6 (sum 10).
The factors we need are 3 and 8, since they sum to 11. This gives us factored form:
(x+3)(x+8)=0.
Using the zero product property, we know that in order to have a product of 0, one or both of the factors must be 0. This means we have:
x+3=0 or x+8=0.
Solving the first equation:
x+3-3=0-3
x=-3.
Solving the second equation:
x+8-8=0-8
x=-8.</span></span>
Step-by-step explanation:
3x-4y=13
y=-3x-7
3x-4(-3x-7)=13
3x+12x+28=13
15x=-15
x= -1
y= -3x-7 = 3-7= -4
( -1, -4)
Answer:
58°F, 20°F,11°F, 2°F , -2°F, -5°F
Answer:
A.
$5352.90
Step-by-step explanation:
A=p(1+r)^t
A=4,000×(1+0.06)^(5)
A=5,352.90
.........................................................
Answer:
The Final Investment Value is
Step-by-step explanation:
we know that
The compound interest formula is equal to
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest in decimal
t is Number of Time Periods
n is the number of times interest is compounded per year
in this problem we have
substitute in the formula above